Biophenolic compounds and metal ions associated with the antioxidant and antibacterial activity of the ethanolic extract of Heliotropium arborescens L. leaves from the Andean region of Ayacucho-Peru - Angel T. Alvarado; Haydee Chávez; Jorge A. García; María R. Bendezú; Felipe Surco-Laos; Aura Molina-Cabrera; Doris Laos-Anchante; Nelly Vega-Ramos; Juan J. Palomino-Jhong; Paulina Eliades Yarasca-Carlos; Berta Loja-Herrera; Mario Pineda-Pérez; et al. (Pensoft Publishers, 2024)
Heliotropium arborescens (Galán de Mera et al. 2022) is a herbaceous plant that contains various biophenolic compounds that exhibit antibacterial property and antioxidant activity that could prevent diseases caused by free radicals. The objective was to study the biophenolic compounds and metal ions associated with the in vitro antioxidant and antibacterial activity of the ethanolic extract of Heliotropium arborescens L. leaves from the Andean region of Ayacucho-Peru. The total polyphenolic content (TPC) was determined by the Folin-Ciocalteu method; Total flavonoid content (TFC) was determined by spectrophotometry at 510 nm, TFC was expressed in mg quercetin/g sample (mg QE/g). Antioxidant activity by three in vitro methods; determination of metals by flame atomic absorption spectrophotometry (FAAS) and antibacterial activity by agar diffusion method. The values ​​obtained from the TPC were 306.80±0.05 mg GAE/g, TFC 111.53±0.25 mg QE/g. Antioxidant activity: DPPH IC50 37.55±0.04 µL and 65.64±0.10 µL, at 0.47 and 0.93 mg/mL extract, respectively; ABTS 0.20±0.01 mM TEAC/g (0.41 mg/mL extract) and 0.47±0.01 (0.82 mg/mL extract); FRAP 0.24±0.01 mM TEAC/g (0.94 mg/mL extract) and 0.46±0.02 mM TEAC/g (1.88 mg/mL extract). Correlation relationship TFC/DPPH (r=0.9994; R2 0.9989), TFC/ABTS (r = 0.9572; R2 0.9998) and TFC/FRAP (r = 09933; R2 0.9868). Calcium 1.22±0.04, copper 0.77±0.05, magnesium 851.7±3.06 and zinc 20.63±1.19 mg/100 g were found in all cases. Antibacterial activity on Bacillus subtilis (ATCC 6633) and Staphylococcus aureus (ATCC 25923) with a minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) > 400 μg/mL. It is concluded that the total biophenolic components and metals of the ethanolic extract of the leaves of H. arborescens L. show potential antioxidant activity, and moderate antibacterial activity against Bacillus subtilis and Staphylococcus aureus. Graphical abstract: